Energy Storage Cell
Patent Information
- Application Number
- JP2024545251
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-16
- Filing Date
- 2023-01-03
- Publication Date
- 2025-02-14
AI Technical Summary
【0036】 被覆が、平面を通る熱伝導性を可能にすると有利である。これにより、電極·セパレータユニットから被覆を通りケーシングに向かう熱伝達を改良することができる。エネルギ貯蔵セルの温度調整は、通常は外部からケーシングを介して行われる。被覆の熱伝導性により、電極·セパレータユニットの熱管理を改善することができる。この場合、熱伝導性は、特に孔が電解質で満たされている場合、熱伝導性が改善される。電解質は通常、比較的高い熱伝導性を有している。さらに、より高温の電極·セパレータユニットと、より低温のケーシングとの間の温度勾配によって、対流により引き起こされる電解質の循環を多孔質の被覆内で達成することができ、この循環は、効果的な温度補償をサポートする。この場合、循環は、温度差の増大と共に強まる。最大に圧縮された状態でも依然として開放孔を有しているフリース材料の繊維架台構造により、この冷却効果は、老朽化したセルにおいても有効である。電解質の熱伝導性と対流の利用により、被覆の繊維材料の可能な断熱特性に関係なく、エネルギ貯蔵セルの熱管理を改善することができる。
Smart Images

Figure 2025504691000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an energy storage cell comprising at least one electrode-separator unit housed within a casing. [Background technology]
[0002] Energy storage systems for electrical energy, in particular rechargeable accumulators, are widely known, especially in mobile systems. Rechargeable accumulators for electrical energy are used, for example, in portable electronic devices, such as smartphones or laptops. Furthermore, rechargeable accumulators for electrical energy are increasingly used to supply electrically driven vehicles with energy. In addition to passenger cars, a wide range of electrically driven vehicles, such as, for example, two-wheelers, vans or trucks, are conceivable here. Likewise, use in robots, ships, aircraft and mobile work machines is conceivable. Further fields of use of electrical energy storage systems are stationary applications, for example in backup systems, network stabilization systems and stationary applications for storing electrical energy from renewable energy sources.
[0003] In this case, the energy storage system often used is a rechargeable accumulator in the form of a lithium-ion accumulator, which, like other rechargeable accumulators for electrical energy, usually has a number of storage cells, which are mounted together in a casing, in which the storage cells, electrically connected to one another, are usually grouped together in a module.
[0004] In this case, the energy storage system does not only refer to lithium-ion accumulators: other rechargeable battery systems such as lithium-sulfur batteries, solid-state batteries, sodium-ion batteries or metal-air batteries are also possible energy storage systems. Furthermore, supercapacitors are also considered as energy storage systems.
[0005] Energy storage systems in the form of rechargeable accumulators have maximum capacitance and best input and output power only within a limited temperature range. Above or below the optimal operating temperature range, the capacity, input and output capabilities of the accumulator are significantly reduced, which impairs the functionality of the energy accumulator. Furthermore, extremely high temperatures can irreversibly damage the energy accumulator. Therefore, it is desirable to avoid both continuous temperature increases and temporary peak temperatures. In the case of lithium-ion accumulators, it is desirable not to exceed continuous temperatures of, for example, more than 50° C. and temporary peak temperatures of more than 80° C.
[0006] Especially for passenger car applications, a rapid charging capability of the energy storage system is required. In this case, it is desirable for the accumulator forming the energy storage system to be fully or almost fully charged within a short time, for example within 15 minutes. Due to the approximately 90% to 95% efficiency of the charging system, a large amount of heat is released in the energy storage system during the charging operation, which needs to be drawn off from the energy storage system. This heat is not released under normal operating conditions. It is therefore necessary to design the cooling system of the energy storage system in such a way that it is able to absorb the amount of heat generated during the charging operation.
[0007] Extremely high temperatures can lead to irreversible damage to the energy storage system. In this context, particularly in the case of lithium-ion batteries, the so-called thermal runaway is known. In this case, a large amount of thermal energy and gaseous decomposition products are released in a short time, which results in high pressures and high temperatures in the casing. This effect is particularly problematic in energy storage systems with a high energy density, such as those required, for example, to supply electrically driven vehicles with electrical energy. Due to the increase in the energy content of the individual cells and the increase in the packing density of the cells arranged in the casing, the problem of thermal runaway is magnified.
[0008] In the region of the runaway cell, the cell casing walls may experience temperatures in the range of 600°C to 1000°C for durations of several minutes. The insulation device must withstand such loads and at the same time reduce the energy transfer to the neighboring cells so that the thermal load of the neighboring cells is at most 150°C. The key is to limit the energy transfer to the neighboring cells and thus prevent them from also going into thermal runaway.
[0009] Particularly in the field of electromobility, there is a need to achieve a high energy density in a small space, which limits the space available for insulating the cells. In order to prevent the individual storage cells from being exposed to excessively high thermal loads, it is also necessary to dissipate the heat emitted by the storage cells. Correspondingly, merely insulating the storage cells is usually not sufficient.
[0010] The key is to ensure thermal compensation between the casing wall and the electrode-separator unit. In this case, heat usually flows from the hotter electrode-separator unit to the cooler casing wall, which may also be cooled directly. The problem here is that an electrically insulating layer, e.g. a plastic film, is usually placed between the two components, and this insulating layer often has a low thermal conductivity. Furthermore, air bubbles can accumulate inside the casing during assembly. These air bubbles form an insulating gas cushion that significantly limits the heat transfer.
[0011] When observed over their service life, lithium-ion storage cells undergo volume changes, increasing in volume over the course of their service life. In the case of pouch-type cells, this is evident, for example, by swelling. In addition, cyclic volume changes occur with each charging or discharging operation. The volume changes of the storage cells must be compensated for by the device. On the one hand, this is done by clamping the storage cells together, which leads to a very large pressure increase. Alternatively, compression elements are arranged between the storage cells, which absorb the volume changes of the storage cells.
[0012] In devices known from the prior art, increasing compression reduces insulation, and heat transfer is generally inversely proportional to the spacing between the storage cells. Summary of the Invention [Problem to be solved by the invention]
[0013] The problem underlying the present invention is to provide an energy storage cell which has improved usage characteristics. [Means for solving the problem]
[0014] This problem is solved by the features of claim 1. Advantageous configurations are given in the dependent claims.
[0015] The energy storage cell according to the invention comprises at least one electrode-separator unit housed in a casing, with a coating at least partially disposed between the electrode-separator unit and the casing, the coating being made of a porous material.
[0016] The construction of the coating from a porous or pore-containing material allows the construction of a coating with elastically insulating and electrically insulating properties, where elastic in the sense of the present invention also means reversibly deformable, but also where the coating is constructed in such a way that it is both electrically insulating and thermally conductive.
[0017] The material may be constructed with open pores, which has the advantage that the coating is suitable for absorbing liquids, in particular electrolytes, which at least partially fill the space between the electrode-separator unit and the casing.
[0018] Preferably, the covering is made elastic. This allows it to compensate for cyclic volume changes of the electrode-separator unit, which may occur on the one hand due to different charge states of the electrode-separator unit and on the other hand due to the life cycle of the electrode-separator unit. Due to its deformation capacity, it is possible to compensate for the increase in volume of the electrode-separator unit when filling with electrolyte. As mentioned above, elasticity also means reversibly deformable.
[0019] The coating may be formed as a cover in the region of the end faces of the electrode-separator unit, in which case the deformable properties make it possible to compensate for manufacturing errors of the electrode-separator unit resulting from the manufacturing process.
[0020] The covering may be made of a fiber structure. In this case, the covering may be made of a fiber sheet structure or a paper-like material, etc. In an advantageous configuration, the covering is made of a nonwoven material. The nonwoven material is a fiber sheet structure that can be manufactured in such a way that it has a porosity, elasticity and deformation capacity optimized for the technical function of the covering while also ensuring the electrical insulation function.
[0021] Due to their fiber-based structure, nonwoven materials have high mechanical strength, which can be improved by additional measures, for example by heat setting, whereby fiber interlacing points are fused together.
[0022] The fleece material has a high tear strength and is resistant to the penetration of particles, which may occur, for example, as a result of processing errors during cell production. If conductive particles penetrate the coating, an electrical short circuit may occur between the electrodes and the wall of the casing. The use of a fleece material advantageously allows such particles to be embedded in the matrix of the fiber structure without the formation of cracks. Due to the fiber structure, the fleece material has a reversible compressibility, which in the case of the coating according to the invention is preferably in the range of 30%. Such a compressibility supports the volume compensation of the electrode-separator unit in the entire range of charge states and also in the case of thickness increases due to aging.
[0023] With a coating thickness of 120 μm and a compression capability of 30%, it can compensate for thickness variations of, for example, 35 μm on each side, or 70 μm total, allowing the coating to absorb typical thickness variations of electrode-separator units in energy storage cells while reducing mechanical compression of the electrode-separator units.
[0024] Pinholes can be avoided if the fiber units have a high uniformity, the fibers of the fiber units have a small fiber diameter, and the porosity is not selected to be excessively high or a large number of layers are realized across the thickness of the coating.
[0025] The covering may be formed from a wet-laid nonwoven. In the case of a wet-laid nonwoven, it is particularly advantageous if the wet-laid nonwoven has a particularly uniform and smooth surface. This is particularly advantageous for the surface facing the electrode-separator unit, since due to the uniform surface it is possible to avoid localized pressure peaks which may lead to cell damage over the long term. In this connection, it is particularly advantageous if the covering has a mechanically deformable configuration, so that the uniformity of the electrode-separator unit can be compensated for. For example, localized expansions which may occur during localized aging phenomena can be compensated for by the covering.
[0026] The fibrous structure may comprise plastic, glass and / or ceramic fibres, which have electrically insulating properties.
[0027] Alternatively, the covering may be made of a spunbond nonwoven, in which case meltblown spunbond nonwovens come into consideration in particular. Due to their manufacture, spunbond nonwovens have particularly few impurities, so that the risk of dirt getting into the energy storage cell is reduced.
[0028] It is also conceivable to form the covering from a dry-laid nonwoven fabric, which can be produced particularly well anisotropically and is therefore suitable for coverings which are exposed to particularly high mechanical loads in one preferred direction.
[0029] Preferably, the porosity of the coating is at most 70%, which makes it possible to ensure that the coating is electrically insulating. The higher the porosity, the higher the compressibility and elasticity. However, in this case, it must always be ensured that the coating is both electrically insulating and to a certain extent thermally conductive.
[0030] Preferably, the average pore size is between 3 μm and 40 μm.Such a configuration results in advantageous properties with respect to electrical insulation, thermal conductivity and elasticity.
[0031] The covering may be formed in multiple layers. Preferably, the covering is formed from at least five, preferably at least eight, fiber layers. In this case, a high mechanical return force is obtained to support the thickness compensation of the electrode-separator unit. The multiple layers ensure the presence of open pores even in the maximally compressed state and also eliminate the occurrence of through holes (pinholes). For a covering thickness of 100 μm, for example, 10 fiber layers each having a thickness of 10 μm can be realized. In this case, the finer fibers improve the uniformity and reduce the risk of through holes. In this case, the fiber structure may consist of fibers with similar fiber diameters or a fiber mixture with thicker structural fibers and finer fibers that improve uniformity. It is also conceivable to use microfibrillated fiber bundles (pulp) as a component that improves uniformity.
[0032] The porosity of the coating creates an additional reservoir for the electrolyte. With a porosity of 50% and a coating thickness of 120 μm, an energy storage cell with dimensions of 250 × 100 × 30 mm requires approximately 3.4 cm 3 This additional electrolyte volume can act against the ageing process of the electrode-separator unit.
[0033] The coating may contain embedded ceramic particles, which can improve the thermal conductivity and also the electrical insulating properties of the coating. Possible are inorganic particles, such as aluminum oxide, aluminum hydroxide or silicon dioxide, which are introduced in particular into the hollow spaces of the fibers. The ceramic filler allows the insulating layer to be constructed in a thermally stable composition. Thus, the heat generated during thermal runaway of the cell does not directly destroy the coating, and the electrical insulation is maintained.
[0034] An electrolyte can be contained within the casing, which is in contact with the sheath. In this case, additional electrolyte can be contained within the casing, since it can be absorbed into the sheath itself through the pores in the material of the sheath. The electrolyte can also improve the thermal conductivity, in particular between the electrode-separator unit and the casing. In this case, compared to a sealed sheath, an additional amount of electrolyte can be introduced into the energy storage cell, which is available as additional storage and which is advantageous in that it leads to improved properties, in particular at the end of the life of the energy storage cell.
[0035] The material of the covering, in particular the fiber material of the covering, can be configured so that it is wettable by the electrolyte arranged in the casing. This can support wetting of the electrode-separator unit, which is particularly advantageous during the filling process. This can be achieved by selecting the fiber material for the covering. For example, polar polymers such as polyamides or polyesters can be wetted by the electrolyte. When using polyolefins, hydrophilization processes, such as gas-phase fluorination, plasma treatment, or stuffing with polar substances, such as acrylic acid, result in a permanently effective wettability for the electrolyte. The application of wetting agents is also conceivable, which in particular accelerates the filling process. Furthermore, it is advantageous in the case of wettable air bubbles that they are dislodged from the cell casing during the filling process, which is not easy to do, for example, with film-based coverings.
[0036] It is advantageous if the covering allows thermal conductivity through the plane. This allows for improved heat transfer from the electrode-separator unit through the covering towards the casing. Temperature regulation of the energy storage cell is usually performed from the outside via the casing. The thermal conductivity of the covering allows for improved thermal management of the electrode-separator unit. In this case, the thermal conductivity is improved, especially if the pores are filled with electrolyte. The electrolyte usually has a relatively high thermal conductivity. Furthermore, due to the temperature gradient between the hotter electrode-separator unit and the colder casing, a circulation of the electrolyte caused by convection can be achieved in the porous covering, which circulation supports an effective temperature compensation. In this case, the circulation intensifies with increasing temperature difference. Due to the fiber scaffolding structure of the fleece material, which still has open pores even in the maximally compressed state, this cooling effect is also effective in aged cells. The exploitation of the thermal conductivity and convection of the electrolyte allows for improved thermal management of the energy storage cell, regardless of the possible insulating properties of the fiber material of the covering.
[0037] Advantageously, the coating can be provided with an adhesive surface, which allows the coating to be applied to the electrode-separator unit during assembly. This makes it possible to avoid the need for additional adhesive tapes, which can become locally thick. Adhesive surfaces based on acrylate binders, for example, come into consideration here.
[0038] In the following, some configurations of the energy storage cell according to the invention will be explained in more detail on the basis of the drawings. [Brief description of the drawings]
[0039] [Figure 1] FIG. 2 is a schematic partial cross-sectional view of an energy storage cell; [Diagram 2] FIG. 1 shows a schematic diagram of an energy storage cell in the form of a prismatic cell. [Diagram 3] FIG. 1 illustrates a schematic of an energy storage cell in the form of a pouch-type cell. [Figure 4]FIG. 1 shows a schematic diagram of an energy storage cell in the form of a cylindrical cell. [Diagram 5] FIG. 1 is a cross-sectional view showing a schematic diagram of an energy storage cell. [Figure 6] FIG. 4 is a cross-sectional view showing a schematic view of a cover. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0040] The figures show an energy storage cell 1 which comprises at least one electrode-separator unit 2 housed in a casing 3. At least partially arranged between the electrode-separator unit 2 and the casing 3 is a coating 4 which is made from a material containing pores.
[0041] In the present invention, the material is made open-porous, and the coating 4 consists of a fiber structure, in particular of a nonwoven material. The coating 4 is made elastic and has a porosity of up to 70%. The average pore size is between 3 μm and 40 μm. The coating 4 has ceramic particles embedded in it. In this case, the thickness of the coating 4 is measured by means of a probe pressing against the surface with a force of 100 kPa. The porosity is obtained from the formula: porosity = (1 - A / (B x C x 1000)) x 100, where A is the weight per unit area (g / m 2 ), B is the density of the material (g / cm 3 ), and C is the thickness.
[0042] An electrolyte is contained within the casing 3 , and the electrolyte is in contact with the coating 4 and is partially absorbed within the coating 4 .
[0043] In FIG. 1 an energy storage cell 1 is shown in a partial cross-section. It can be seen that a covering 4 is arranged between a casing 3 and an electrode-separator unit 2. In this case, the covering 4 embeds the electrode-separator unit 2, forms an electrical insulation between the casing 3 and the electrode-separator unit 2, forms a thermally conductive connection between the casing 3 and the electrode-separator unit 2 and compensates the volumetric changes of the electrode-separator unit 2 by its elasticity. Furthermore, the bottom area of the energy storage cell 1 is also covered by a covering 4.
[0044] In Fig. 2 an energy storage cell 1 in the form of a prismatic cell is shown. In Fig. 3 an energy storage cell 1 in the form of a pouch cell is shown. In Fig. 4 an energy storage cell 1 in the form of a cylindrical cell is shown.
[0045] In figure 5 an energy storage cell 1 is shown in cross section. In this configuration a coating 4 covers the electrode-separator unit 2 on the side and bottom areas.
[0046] In an alternative configuration, the covering 4 covers the electrode-separator unit 2 in the side regions, the bottom region and the lid region. An additional bottom part, which may be formed in a form-stable manner, may be arranged correspondingly at the bottom. An additional lid part may be arranged correspondingly at the lid. The lid part and / or the bottom part may be arranged between the casing 3 and the electrode-separator unit 2. In this case, the covering 4 may additionally extend between the bottom part and / or the lid part and the casing 3 and / or the electrode-separator unit 2.
[0047] In Fig. 6 the wall of the covering 4 is shown in a detailed cross-section. In this configuration, the covering 4 is formed from a nonwoven fabric. In this case, the nonwoven fabric may be formed as a meltblown nonwoven fabric or a wet-laid nonwoven fabric. In a first option, the nonwoven fabric is single-ply, in a second option, the nonwoven fabric is multi-ply, in particular 5-ply or 8-ply. Various configurations of the nonwoven fabric of the covering 4 are now specifically described. EXAMPLES
[0048] Weight per unit area is 60g / m 2 A wet-laid polyolefin nonwoven fabric based on polypropylene and polyethylene is prepared with a thickness of 120 μm at 200 sq. m. The air permeability of the wet-laid nonwoven fabric is 220 l / sm at a differential pressure of 2 mbar. 2 The wet-laid nonwoven is stiffened by thermal bonding and by the use of core-clad binder fibers. Particularly for lithium-ion accumulators, the use of polyolefins is advantageous because they are stable with respect to the accumulator materials. The wet-laid nonwoven is wrapped around the electrode-separator unit 2 to form the covering 4. EXAMPLES
[0049] Weight per unit area is 60g / m 2 A wet-laid polyolefin nonwoven fabric based on polypropylene and polyethylene is prepared with a thickness of 120 μm at 200 sq. m. The air permeability of the wet-laid nonwoven fabric is 220 l / sm at a differential pressure of 2 mbar. 2 The wet-laid nonwoven is stiffened by thermal bonding and by the use of core-clad binder fibers. In particular for lithium-ion accumulators, the use of polyolefins is advantageous because they are stable with respect to the accumulator materials. The surface of the wet-laid nonwoven is made permanently hydrophilic by gas-phase fluorination. The use of fluorinated polyolefins is advantageous in particular in connection with the use in alkaline battery systems, e.g. nickel metal hydride accumulators. The wet-laid nonwoven is wrapped around the electrode-separator unit 2 to form the covering 4. EXAMPLES
[0050] Weight per unit area is 63g / m 2A polyolefin wet-laid nonwoven fabric based on polypropylene and polyethylene with a thickness of 140 μm is prepared at 2000 rpm. The surface of the wet-laid nonwoven fabric is permanently hydrophilized by gas-phase fluorination. The wet-laid nonwoven fabric is wrapped around the electrode-separator unit 2 to form a coating 4. EXAMPLES
[0051] Weight per unit area is 50g / m 2 A polyester wet-laid nonwoven fabric based on polyethylene terephthalate (PET) and polybutylene terephthalate (PBT) is prepared with a thickness of 95 μm at 200 sq. m. The air permeability is 500 l / sm at a differential pressure of 2 mbar. 2 The material is heat cured by thermal bonding and the use of core-clad binder fibers. Compared to polyolefins, polyester-based plastics have a higher heat resistance. The wet-laid nonwoven fabric is wrapped around the electrode-separator unit 2 to form the covering 4. EXAMPLES
[0052] A polyamide wet-laid nonwoven fabric based on polyamide 6.6 and polyamide 6 is prepared. The weight per unit area is 67 g / m. 2 and has a thickness of 120 μm. The material is heat-set by thermal bonding and the use of core-clad binder fibers. Polyamide certainly has a relatively high expansion coefficient in relation to the lithium electrolyte. However, this can be advantageous in relation to the sheath 4, since this embeds the electrode-separator unit 2 within the sheath 4. The wet-laid nonwoven is wrapped around the electrode-separator unit 2 to form the sheath 4. EXAMPLES
[0053] A meltblown nonwoven fabric based on polypropylene is prepared. The weight per unit area is 43 g / m. 2and has a thickness of 110 μm. Bonding is done by thermal bonding in situ at the time of fiber laying. The material is then calendered. The wet-laid nonwoven is wrapped around the electrode-separator unit 2 to form the covering 4. EXAMPLES
[0054] A wet-laid nonwoven fabric based on polyphenylene sulfide (PPS) is prepared. The weight per unit area is 60 g / m. 2 and has a thickness of 105 μm. Thermal bonding is achieved by calendaring. The wet-laid nonwoven fabric is wrapped around the electrode-separator unit 2 to form the coating 4. EXAMPLES
[0055] A polyolefin wet-laid nonwoven fabric is provided that includes core-clad binder fibers having a core made of polypropylene and a clad made of polyethylene. The fiber blend of the core-clad fibers further includes highly fibrillated polypropylene pulp. The nonwoven fabric formed therefrom has a fiber density of 55 g / m 2 The wet nonwoven fabric has a weight per unit area of 180 l / sm at a pressure difference of 2 mbar and a thickness of 110 μm. 2 The wet nonwoven fabric is cured by thermal bonding, where the highly fibrillated pulp does not melt at the curing temperature. The wet nonwoven fabric is wrapped around the electrode-separator unit 2 to form the coating 4. EXAMPLES
[0056] Weight per unit area is 70g / m 2A spunbond nonwoven based on polyethylene terephthalate (PET) is prepared with a thickness of 130 μm at 2000 rpm. Consolidation is performed by thermal bonding using a calendar process. The spunbond nonwoven is wrapped around the electrode-separator unit 2 to form the cover 4. Spunbond nonwovens are advantageous for this application because they can be produced in a clean process that is contamination-protected. EXAMPLES
[0057] A spunbond nonwoven fabric based on polyethylene terephthalate (PET) and polyethylene terephthalate copolymer (coPET) in the form of core-clad fibers is prepared. The nonwoven fabric has a density of 80 g / m 2 and a thickness of 140 μm. Consolidation is performed by thermal bonding using a calendaring process. The spunbond nonwoven is wrapped around the electrode-separator unit 2 to form the coating 4. EXAMPLES
[0058] A spunbond nonwoven fabric based on polypropylene (PP) is prepared. The nonwoven fabric has a density of 60 g / m 2 and a thickness of 100 μm. Consolidation is performed by thermal bonding via calendaring. The spunbond nonwoven is wrapped around the electrode-separator unit 2 to form the coating 4. EXAMPLES
[0059] Weight per unit area is 60g / m 2 A dry nonwoven fabric based on polyethylene terephthalate (PET) is prepared with a thickness of 85 μm at 1000 nm. The hardening is carried out by thermal bonding using a calendar process. The dry nonwoven fabric is wrapped around the electrode-separator unit 2 to form the coating 4.
[0060] In another configuration, a nonwoven fabric based on glass fibers or a woven fabric made of silica fibers is used. In addition to fibers, the coating 4 may contain fibrillated fillers (pulp). The fibrillated fillers reduce the diameter of the pores of the coating 4 and at the same time increase the surface area.
[0061] The above-mentioned materials have a relatively low porosity and a uniform pore structure. This is achieved by a high degree of predetermined compaction of the material during thermal bonding or calendering. Furthermore, fibers with small fiber diameters of 1 μm to 15 μm are used. The production of the coating 4 by wet-laid or melt-blown processes allows for a particularly uniform nonwoven structure.
[0062] To form the coating 4, the material may be present in the form of a strip-like layer that is wound around the electrode-separator unit 2. In this case, the width of the layer corresponds approximately to the height of the electrode-separator unit 2.
[0063] In the case of plug-in electrode-separator units 2, which are used especially for pouch-type or prismatic cells, the construction of a covering 4 in the form of a cover layer on both sides of the electrode-separator unit 2 is also conceivable.
[0064] It is also conceivable to attach the covering 4 to the side of the electrode-separator unit 2 which has a pole through-guide. In this case, breaks can be introduced into the covering 4 in the region of the pole through-guide.
[0065] The covering 4 can be attached to the bottom plate, which can be a fully plastic component, a plastic component with cutouts, a rack-shaped plastic component or a structure based on nonwoven material. If burst openings are located in the area of the bottom plate in the cell casing, it is advantageous to provide corresponding cutouts in the bottom plate at this location. In principle, it is also conceivable to provide a ceramic bottom plate. In this case, it should be noted that the electrode-separator unit 2 is securely fastened to the bottom plate, which ensures a reliable electrical insulation of the electrode-separator unit 2. The connection of the covering 4 to the bottom plate can be carried out, for example, by gluing or welding.
[0066] The covering 4 can be attached to the cover plate. In this case, the cover plate can be a fully-covered plastic component, a plastic component with cutouts, a plastic component in the form of a frame or a structure based on nonwoven material. In principle, it is also conceivable to provide a ceramic bottom plate. If a burst opening is located in the area of the cover plate in the cell casing, it is advantageous to provide a corresponding cutout in the cover plate at this location. It should be noted in this case that the electrode-separator unit 2 is securely fastened to the cover plate, which ensures a reliable electrical insulation of the electrode-separator unit 2. The connection of the covering 4 to the cover plate can be carried out, for example, by gluing or welding.
Claims
1. 1. An energy storage cell (1), comprising at least one electrode-separator unit (2) housed in a casing (3), with a coating (4) at least partially arranged between the electrode-separator unit (2) and the casing (3), the coating (4) being made of a porous material.
2. The energy storage cell of claim 1 , wherein the material is configured with open porosity.
3. 3. The energy storage cell according to claim 1, wherein the coating (4) is elastically configured.
4. 4. The energy storage cell according to claim 1, wherein the coating (4) is made of a textile structure.
5. 5. The energy storage cell according to claim 1, wherein the covering (4) is made of a non-woven material.
6. 5. Energy storage cell according to claim 1, wherein the coating (4) is made of a wet-laid, dry-laid and / or spunbonded nonwoven fabric.
7. 7. Energy storage cell according to any one of claims 4 to 6, wherein the fibrous structure comprises plastic fibres, glass fibres and / or ceramic fibres.
8. 8. Energy storage cell according to any one of the preceding claims, characterized in that the porosity of the coating (4) is at most 70%.
9. The energy storage cell according to any one of claims 1 to 8, wherein the average pore size is between 3 μm and 40 μm.
10. 10. Energy storage cell according to claim 1, characterized in that the coating (4) is formed in multiple layers.
11. 11. Energy storage cell according to claim 10, wherein the coating (4) comprises at least five fibre layers.
12. 12. Energy storage cell according to any one of the preceding claims, characterized in that the coating (4) has ceramic particles embedded therein.
13. 13. Energy storage cell according to any one of the preceding claims, characterized in that an electrolyte is contained within the casing (3), which is in contact with the coating (4).
14. 14. Energy storage cell according to claim 13, characterized in that the material of the coating (4) is provided such that the coating (4) is wettable by the electrolyte.
15. 15. Energy storage cell according to claim 13 or 14, wherein the electrolyte is in contact with the casing (3) and the electrode-separator unit (2).
16. 16. Energy storage cell according to any one of claims 13 to 15, wherein the electrolyte is circulatable within the coating (4).
17. 17. Energy storage cell according to any one of claims 13 to 16, wherein the coating (4) permeated with the electrolyte has a thermal conductivity of at least 0.4 W / (m*K).
18. 18. Energy storage cell according to any one of the preceding claims, wherein the coating (4) is provided with an adhesive layer on the side facing the electrode-separator unit (2).
19. 19. Energy storage cell according to claim 1, characterized in that a bottom plate and / or a cover plate are arranged correspondingly on the covering (4).
20. 20. Energy storage cell according to claim 19, characterized in that the coating (4) is guided at least partially around the periphery of the base plate and / or the cover plate.
Citation Information
Patent Citations
Alkaline secondary battery
JP2000082490A
Alkaline storage battery
JP2000164192A
Separator for battery
JP2003109569A
Battery
JP2009252397A
Battery
JP2009301892A